2005
DOI: 10.4321/s0213-61632005000400005
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid adjustment and previous personality in schizophrenic patients

Abstract: Psychosocial adjustment and premorbid personality are two factors that are frequently studied in order to elucidate the etiopathogenesis of schizophrenia. Premorbid adjustment alterations and personality disorders (principally those of the schizophrenia spectrum) have been considered vulnerability elements or have been linked with the early manifestations of a disease that is still underdeveloped (hypothesis of neurodevelopment). In this paper we review the literature. We also studied the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…Partly corroborating our first and second hypotheses, we found poor PA social as a composite measure and in early and late adolescence to associate with higher prevalence of comorbid personality disorders. This corroborates studies from the schizophrenia population finding this association to be specifically linked to deficits in early adolescence (Castle et al, 1993; McGlashan, 1986; Solano & de Chávez, 2005). The possible specific importance of impairments in early adolescent PA social for later pathological adversities is reflected in the finding of this being linked to transition to psychosis and development of schizophrenia (Dragt et al, 2011; Tarbox et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Partly corroborating our first and second hypotheses, we found poor PA social as a composite measure and in early and late adolescence to associate with higher prevalence of comorbid personality disorders. This corroborates studies from the schizophrenia population finding this association to be specifically linked to deficits in early adolescence (Castle et al, 1993; McGlashan, 1986; Solano & de Chávez, 2005). The possible specific importance of impairments in early adolescent PA social for later pathological adversities is reflected in the finding of this being linked to transition to psychosis and development of schizophrenia (Dragt et al, 2011; Tarbox et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Two studies found links between poor PA social in early adolescence and conversion to psychosis in UHR individuals (Dragt et al, 2011; Tarbox et al, 2013) with the specific finding of early adolescent PA social predicting the development of schizophrenia versus other psychotic disorders (Tarbox et al, 2013). Regarding established psychotic disorders, studies link poor PA social to comorbid disorders like social anxiety, substance use, affective, and premorbid personality disorders (Castle et al, 1993; McGlashan, 1986; Solano & de Chávez, 2005). Existing literature reports no associations between psychiatric diagnoses and PA academic except for a review on substance use disorders linking these to worse PA academic but better PA social (Prat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of research exists concerning premorbid social functioning in schizophrenia that has been derived from both retrospective and longitudinal studies in an attempt to differentiate personality markers for developing psychosis. Poorer premorbid social adjustment in individuals with schizophrenia than controls has been evidenced in many of these investigations [15][16][17] . Premorbid adjustment was also related to social skill level within schizophrenia 18 .…”
mentioning
confidence: 99%